Bismuth composition for metal pretreatment application

By forming a bismuth conversion coating on the metal surface, the environmental pollution and energy consumption problems of traditional zinc phosphate coatings are solved, and corrosion protection and paint layer adhesion are provided comparable to it, which is suitable for a variety of metal surfaces.

JP2025020181APending Publication Date: 2025-02-12HENKEL KGAA
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024186567
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-02-14
Filing Date
2024-10-23
Publication Date
2025-02-12

AI Technical Summary

Technical Problem

Existing chemical coating technology has problems of environmental pollution and high energy consumption in improving metal corrosion protection and paint layer adhesion. In particular, traditional zinc phosphate coatings contain heavy metals and produce hazardous waste, which is difficult to meet the requirements of the automobile industry.

Method used

A bismuth-based conversion coating composition was developed, by forming a bismuth conversion coating on the metal surface, using an aqueous bismuth chemical coating composition containing dissolved and dispersed bismuth, water-soluble organic chelating agent, copper ions and acid regulators, avoiding the use of heavy metals and phosphates and reducing the operating temperature.

Benefits of technology

It achieves corrosion protection and paint adhesion comparable to traditional zinc phosphate coatings, while reducing environmental pollution and energy consumption. It is suitable for a variety of metal surfaces, including automobiles, energy equipment, agricultural machinery, buildings and household appliances.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025020181000001
    Figure 2025020181000001
  • Figure 2025020181000002
    Figure 2025020181000002
  • Figure 2025020181000003
    Figure 2025020181000003
Patent Text Reader

Abstract

To provide a chemical conversion coating capable of reducing or avoiding the disadvantageous points of a zinc phosphate process while achieving corrosion resistance and coating adhesiveness equivalent to tri-cationic zinc phosphate chemical conversion coating.SOLUTION: An acidic aqueous bismuth chemical conversion coating composition including A) dissolved and / or dispersed bismuth, B) at least one water-soluble organic chelate agent existing in an amount sufficient to dissolve or disperse A) and C) dissolved copper ions has a pH of approximately 2.0 to approximately 6. Provided are a method for manufacturing the bismuth chemical conversion coating composition, a method for vapor-depositing the bismuth chemical conversion coating on a metal substrate and a product having a metal surface including the bismuth chemical conversion coating.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to bismuth compositions, such as conversion coating compositions for metal pretreatment applications, such as deposition on metal surfaces to improve corrosion resistance and / or paint adhesion, methods of making said compositions, methods of coating metal substrates, and articles having metal surfaces coated with the compositions. [Background technology]

[0002] Many consumer and industrial products are formed from metal substrates and are exposed to the elements. As such, these metal products are exposed to corrosive environments. As such, they are often coated with protective coatings, including anticorrosive coatings and paints. Many such anticorrosive coatings are known as conversion coatings, and are understood in the art to be coatings formed by contacting a metal surface with a reactive coating composition, thereby forming a conversion coating thereon. These conversion coatings improve the corrosion resistance of metals, but further improvements in conversion coatings are a continuing market requirement for automotive and white goods applications.

[0003] A typical process for applying a conversion coating layer onto a metal substrate includes the steps of cleaning, rinsing, depositing, and optionally post-rinsing and / or sealing the conversion coating. The metal substrate, now at least partially coated with a conversion coating layer, is then most often subjected to a painting step (e.g., by electrophoretic coating, also known as E-coating).

[0004] Conventional tricationic zinc phosphate conversion coating systems provide excellent corrosion resistance and paint adhesion, but contain undesirable heavy metals and generate environmentally harmful waste through the precipitation of heavy metal phosphate sludges. These sludges, as well as overflows from zinc phosphate baths, contain high concentrations of phosphate ions, both of which can contribute to the eutrophication of natural water supplies. Zinc phosphate baths also operate at high temperatures, requiring increased energy usage. It would therefore be desirable to reduce or avoid the disadvantages of the zinc phosphate process while achieving comparable corrosion resistance and paint adhesion. Zirconium-based conversion coatings have been proposed as an alternative to tricationic zinc phosphate, but in some applications these conversion coatings do not meet industry requirements, particularly those of the automotive industry. Summary of the Invention [Problem to be solved by the invention]

[0005] Therefore, the development of alternative conversion coatings and methods would be highly desirable. [Means for solving the problem]

[0006] A bismuth conversion coating composition has been developed that deposits a bismuth conversion coating on a metal substrate. Metal substrates pretreated with the aqueous bismuth conversion coating composition and subsequently coated with paint, particularly an E-coat paint, exhibited comparable improved corrosion resistance and paint adhesion compared to a tricationic zinc phosphate control.

[0007] The bismuth conversion coating composition may be applied to the metal surface of the substrate by dipping (immersing) the metal substrate in the aqueous solution or by spraying the solution onto the metal substrate. Alternatively, the coating composition can be applied by roll coating or other known conversion coating deposition techniques.

[0008] Preferred embodiments of the bismuth conversion coating composition provide bismuth conversion coatings with corrosion resistance and paint adhesion comparable to conventional tricationic zinc phosphate compositions, and improve reduced environmental impact due to: absence of heavy metals, e.g., Zn, Ni, and Mn; absence of phosphorus; and reduced operating temperatures.

[0009] Some applications of the bismuth conversion coating composition include coating metal substrate surfaces, such as iron, zinc-containing, aluminum-containing surfaces, and combinations thereof, which are subsequently painted and require paint adhesion and corrosion resistance.Suitable applications may include automotive OEM (body in white), transportation such as auto parts; energy industry such as wind and solar equipment; agricultural and construction machinery; recreational vehicles; construction; household products such as appliances; office furniture; metal coils; metal containers, etc.

[0010] According to one aspect of the present invention ("Aspect 1"), A) Dissolved and / or dispersed bismuth, B) at least one water-soluble organic chelating agent present in an amount sufficient to solubilize or disperse A); C) dissolved copper ions; A conversion coating composition is provided that comprises, consists essentially of, or consists of an acidic aqueous bismuth conversion coating composition comprising:

[0011] Example 2: The acidic aqueous bismuth conversion coating composition as described in Example 1, wherein A) comprises at least one dissolved Bi(III) and dissolved and / or dispersed bismuth compounds; and B) comprises one or more water soluble organic acids and salts thereof.

[0012] Aspect 3: The acidic aqueous bismuth conversion coating composition as described in Aspect 2, wherein the one or more water soluble organic acids and salts thereof are selected from aliphatic or aromatic; linear, branched or cyclic; saturated or unsaturated C3-C12 organic acids and salts thereof.

[0013] Example 4: The acidic aqueous bismuth conversion coating composition of Example 2, wherein the one or more water-soluble organic acids and salts thereof comprise at least one organic polycarboxylic acid and salts thereof.

[0014] Aspect 5: The acidic aqueous bismuth conversion coating composition of aspect 4, wherein the at least one organic polycarboxylic acid and salt thereof comprises a substituted and / or unsubstituted alpha, omega-dicarboxylic acid.

[0015] Aspect 6: The acidic aqueous bismuth conversion coating composition as described in aspect 5, wherein the substituted and / or unsubstituted alpha, omega-dicarboxylic acids and salts thereof comprise one or more substituted and / or unsubstituted propanedioic acid, butanedioic acid, pentanedioic acid, hexanedioic acid, heptanedioic acid, octanedioic acid, nonanedioic acid, decanedioic acid, and salts thereof.

[0016] Example 7: The acidic aqueous bismuth conversion coating composition as described in Example 2, wherein the one or more water-soluble organic carboxylic acids and salts thereof include tartaric acid and salts thereof.

[0017] Embodiment 8: The acidic aqueous bismuth conversion coating composition as described in embodiment 1, comprising less than 1 wt. % of a phosphorus-containing acid and / or salt thereof and less than 1 wt. % of nickel.

[0018] Example 9: The acidic aqueous bismuth conversion coating composition of Example 1, comprising one or more additional components selected from the group consisting of free fluoride, nitrate, and a source of Si-based material.

[0019] Example 10: The acidic aqueous bismuth conversion coating composition as described in Example 1, wherein the acidic aqueous bismuth conversion coating composition includes at least one pH adjuster and has a pH of about 2.5 to about 5.0.

[0020] Example 11: The acidic aqueous bismuth conversion coating composition of Example 1, wherein the dissolved and / or dispersed bismuth is present in a total concentration of about 5 to 10,000 ppm.

[0021] Example 12: The acidic aqueous bismuth conversion coating composition of Example 1, wherein the dissolved and / or dispersed bismuth comprises one or more of a nitrate, an oxide, and a hydroxide of bismuth.

[0022] Aspect 13: The acidic aqueous bismuth conversion coating composition as described in Aspect 1, wherein the dissolved and / or dispersed bismuth is selected from bismuth nitrate, bismuth nitrate pentahydrate, bismuth subnitrate, bismuth oxide, bismuth hydroxide, and combinations thereof.

[0023] Example 14: The acidic aqueous bismuth conversion coating composition of Example 1, wherein the at least one water soluble organic chelating agent is present in a total concentration of about 50 to 100,000 ppm.

[0024] Embodiment 15: Another embodiment of the present invention comprising, consisting essentially of, or consisting of a replenisher composition for replenishing the acidic aqueous bismuth conversion coating composition described above after use, comprising a storage stable composition comprising bismuth, copper, nitric acid, and optionally a nitrate salt.

[0025] Aspect 16: a) contacting a metal surface of a substrate, preferably selected from iron metals, zinc-containing metals, and aluminum-containing metals, with the acidic aqueous bismuth conversion coating composition described above for a time sufficient to form a bismuth conversion coating layer on at least a portion of the metal surface; and b) rinsing the bismuth conversion coating layer with a rinse solution comprising water;

[0023] Another aspect of the present invention comprises, consists essentially of, or consists of a method of depositing a bismuth conversion coating on a substrate having a metallic surface, comprising:

[0026] Example 17: The method of depositing a bismuth conversion coating of Example 16, further comprising step c) coating at least a portion of the metal surface having the bismuth conversion coating layer with a cathodically depositable electrophoretic dip coating, wherein after the rinsing step b), the metal surface is not dried before being coated with the cathodically depositable electrophoretic dip coating.

[0027] Embodiment 18: Another embodiment of the present invention comprising, consisting essentially of, or consisting of a substrate having a metal surface having a bismuth conversion coating layer deposited thereon, the bismuth conversion coating layer comprising bismuth oxide and / or bismuth hydroxide, and further comprising at least one of the elements Cu, Cu(I), and Cu(II).

[0028] Aspect 19: According to yet another aspect of the present invention, there is provided a conversion coating composition comprising, consisting essentially of, or consisting of an acidic aqueous bismuth conversion coating composition comprising: A) Dissolved and / or dispersed bismuth; B) a complex fluoroacid, preferably fluorosilicic acid, present in an amount sufficient to solubilize or disperse A); C) dissolved copper ions; and At least one pH adjusting agent in the form of an acid, base, or buffer acid / base combination present in an amount sufficient to provide the composition with a pH in the range of about 2.0 to 6.0.

[0029] Unless specifically stated otherwise, any combination or sub-combination of the above aspects is considered to be within the scope of the present invention.

[0030] For various reasons, it is preferred that the aqueous bismuth conversion coating composition according to the present invention, as defined above, is substantially free of many of the components used in compositions for similar purposes in the prior art. Specifically, it is increasingly preferred that the aqueous composition according to the present invention contains not more than 1.0, 0.5, 0.35, 0.10, 0.08, 0.04, 0.02, 0.01, 0.001, or 0.0002% of each of the following components, more preferably the said values ​​in grams per liter, and most preferably the values ​​in ppm, when in direct contact with the metal in the process according to the present invention, independently for each of the preferably minimized components listed below: zinc, nickel, cobalt, manganese, ... Cancer, chromium, cyanide, nitrite ions, organic surfactants, formaldehyde, formamide, urea, hydroxylamine, ammonia, tertiary amines, cyclic amines such as hexamethylenetetraamine; silicates, siloxanes, organosiloxanes, silanes; lanthanide metals, rare earth metals; phosphorus-containing acids and / or their salts; sulfur, such as sulfates, sulfonic acids; permanganates; perchlorates; boron, such as borax, borates; strontium; and / or free chloride.

[0031] It is also increasingly preferred that, independently for each of the preferably minimized components listed below, the as-deposited bismuth conversion coatings and as-deposited post-treatments according to the present invention contain no more than 1.0, 0.5, 0.35, 0.10, 0.08, 0.04, 0.02, 0.01, 0.001, or 0.0002%, more preferably the aforementioned values ​​in parts per thousand (ppt), of each of the following components: chromium, cyanide, nitrite ions, organic surfactants, formaldehyde, formamide, urea, hydroxylamine, ammonia, hexamethylenetetraamine; silicates, siloxanes, organosiloxanes, silanes; rare earth metals; phosphorus-containing acids and / or salts thereof; sulfur, e.g., sulfates, sulfonic acids; permanganates; perchlorates; boron, e.g., borax, borates; strontium; and / or chloride.

[0032] Some materials may be present in the bismuth conversion coating working bath due to, for example, drag-in from previous process steps, leaching from the substrate, inclusion as counterions or contaminants. Non-limiting examples of materials not intentionally added to the bath that may be present and are desirably minimized include phosphates and silicates from cleaner drag-in; free Cl ions that may be present from water contamination, Fe, Zn, and Al ions leaching from the substrate. Counterions that may be present include ammonia or ammonium ions, alkali metals (NH 4 + , Na + , K + ), sulfates, etc.

[0033] The term "paint" includes all similar materials that may be designated by more technical terms such as lacquer, enamel, varnish, shellac, topcoat, etc., unless otherwise specified or necessarily implied by the context. The simple terms "metal" or "metallic" will be understood by those skilled in the art to mean a material, whether an article or a surface, composed of atoms of metallic elements, e.g., iron, zinc, etc., the sum of the metallic elements present in an amount of increasing priority in the order of at least 55, 65, 75, 85, or 90 atomic %. The simple term "iron" includes pure iron and its alloys (such as steel), and similarly "zinc-containing" and "aluminiferous" include the pure metal and their respective alloys.

[0034] Except in the operating examples or where otherwise indicated, all numbers defining amounts of ingredients, reaction conditions, or ingredient parameters used herein should be understood to be modified in all instances by the term "about." Throughout the description, unless otherwise indicated, percent, "parts," and ratio values ​​are by weight or mass; the description of a group or class of materials as suitable or preferred for a given purpose in connection with the present invention means that mixtures of any two or more members of the group or class are equally suitable or preferred; the description of components in chemical terms refers to the components upon addition to any combination specified in the description, or upon production in situ within the composition by chemical reaction between one or more newly added components and one or more components already in the composition when other components are added; the specification of a component in ionic form further implies the presence of sufficient counterions to produce electrical neutrality of the composition as a whole and of any material added to the composition; counterions so expressly specified are preferably explicitly specified in ionic form. counterions are selected as far as possible from among the other components specified; otherwise, such counterions may be freely selected, except to avoid counterions which act detrimentally to the purposes of the present invention; molecular weight (MW) is weight average molecular weight; the word "mole" means "gram mole" and the word itself and all of its grammatical variations may be used for chemical species defined by all types and numbers of atoms present therein, regardless of whether the species is ionic, neutral, unstable, hypothetical or actually a stable neutral substance with a well-defined molecule; the term "storage stable" should be understood to include solutions and dispersions in which the material shows no tendency for visually detectable phase separation over an observation period of at least 100 hours undisturbed mechanically, or preferably at least 1000 hours, and the temperature of the material is maintained at ambient room temperature (18-25°C).

[0035] Organic materials are understood to refer to molecules composed of at least one carbon atom to which a hydrogen is attached, which may form chain or ring structures and may optionally contain additional attached atoms and functional groups (e.g. oxygen, silicon, phosphorus and nitrogen).

[0036] These and other features and advantages of the present invention will become more apparent to those skilled in the art from a detailed description of the preferred embodiments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0037] The present invention provides a bismuth conversion coating composition useful for coating a metal substrate surface, the aqueous acidic bismuth conversion coating composition comprising, or in some cases consisting essentially of, or in some cases consisting of the following mixture: A) dissolved and / or dispersed bismuth, optionally dissolved and / or dispersed bismuth compounds, preferably containing Bi(III) ions; B) at least one water-soluble organic chelating agent, which desirably comprises one or more water-soluble organic acids capable of chelating, and preferably increasing the solubility of, the dissolved and / or dispersed bismuth, and may have a pH in the range of about 2.0 to about 6; C) copper(II) ions; D) at least one metal etchant, desirably including a source of free fluoride, e.g., a fluoride-containing compound such as HF and / or a complex fluoro acid that can provide a reservoir of free fluoride ions. The free and complex fluoride ions act to increase etching of the metal substrate surface; E) at least one pH adjusting agent in the form of an acid, base, or buffer acid / base combination useful for adjusting the pH to the ranges of 2-6, 2.5-5, 2.75-4.5, 3-4; Optional ingredients of the bismuth conversion coating composition include: F) nitrate ion; G) IVB group metals: Zr, Ti, Hf; H) at least one accelerator; and I) At least one water-soluble and / or water-dispersible polymeric compound.

[0038] The aqueous mixture may be in the form of a solution or dispersion, preferably a storage stable solution or dispersion. As used herein, the term "dispersion" encompasses mixtures in which none of the components of the mixture are dissolved in the aqueous medium, as well as mixtures in which one or more components of the mixture are partially dissolved in the aqueous medium.

[0039] Component A), the dissolved and / or dispersed bismuth, desirably comprises dissolved Bi(III), but may be provided from dissolved bismuth metal, dissolved and / or dispersed bismuth compounds, or, desirably, from Bi(V), using a reducing agent useful for lowering the oxidation state of the bismuth to Bi(III). Some sources of bismuth may be relatively insoluble in water and may be useful in the present invention by first dissolving in an acid or adjusting the pH of the conversion coating composition. An illustrative, non-limiting example of a bismuth source is bismuth nitrate Bi(NO 3 ) 3 ; Bismuth nitrate pentahydrate Bi(NO 3 ) 3 5H 2 O; Bismuth subnitrate Bi 5 O(OH) 9 (NO 3 ) 4 ; Bismuth oxide Bi 2 O 3 ;Bismuth hydroxide Bi(OH) 3 ; Bismuth aluminate Bi 2 (Al 2 O 4 ) 3 ;Bismuth ammonium citrate C 12 H 22 BiN 3 O 14 ;Bismuth citrate BiC 6 H 5 O 7 (1:1); Bismuth C subcitrate 12 H 8 BiK 5 O 14 ; Sodium bismuth tartrate (C 4 H 4 O 6 ) 2BiNa; Bismuth sodium triglycolate C 24 H 28 BiN 4 Na 7 O 25 , bismuth nitrilotriacetate complex sodium salt; bismuth triacetate CH 3 COOBiO; Bismuth subcarbonate (basic bismuth carbonate) (BiO) 2 CO 3 ; Bismuth carbonate Bi 2 (CO 3 ) 3 ;Bismuth fluoride BiF 3 ; Bismuth molybdate Bi 2 (MoO 4 ) 3 ;Bismuth subsalicylate HOC 6 H 4 COOBiO(1:1 or 3:1); Bismuth sulfate Bi 2 (SO 4 ) 3 ;Bismuth silicate Bi 4 S 3 O 12 , complex silicate; bismuth hydroxide Bi(OH) 3 ; Bismuth tungstate Bi 2 (WO 4 ) 3 ; Bismuth vanadate BiVO 4 Illustrative, non-limiting examples of suitable bismuth sources include the Bi compounds bismuth oxide, bismuth sulfate, bismuth nitrate, bismuth nitrite, and similar at least partially water-soluble and / or acid-soluble bismuth materials.

[0040] For example, bismuth(V) phosphate, Bi 3 (PO 4 ) 5 ;Bismuth(III) orthophosphate, BiPO 4 ;Bismuth bromide, BiBr 3、 BiOBr; bismuth halogens such as bismuth oxybromide, BiOBr; bismuth pentafluoride, BiF 5 ;Bismuth trihydride, BiH 3 ;Bismuth chloride, BiCl 3;Bismuth oxychloride, BiOCl;Bismuth iodide, Bii 3 ; bismuth oxyiodide, BiOI; and sodium bismuthate, NaBiO, which is also insoluble. 3 ; Bismuth oxalate, Bi(C 2 O 4 ) 3 ; Bismuth oleate, [CH 3 (CH 2 ) 7 CH=CH(CH 2 ) 7 COO] 3 Bi; Similarly, when dissolved in acid, H 2 Bismuth butylthiolaurate, which can release S gas, CH 39 (CH 2 ) 9 CH(SC 4 H 9 )COOBi(OH) 2 and bismuth sulfide Bi 2 S 3 Other sources of Bi that are gas generants such as Bi can be used, but tend to be less desirable due to their counter ions, environmental impact, and / or safety reasons.

[0041] As disclosed herein, any inorganic or organic source of Bi(III) in the working bath may be used that provides Bi(III) that can be deposited as a conversion coating on a metal substrate and does not adversely affect the objects and benefits of the present invention. Combinations of two or more different bismuth compounds may be used.

[0042] Bismuth conversion coating compositions useful in the present invention may have, for example, a concentration of component A) dissolved and / or dispersed bismuth of about 5-10,000 ppm, 15-5000 ppm, 25-4000 ppm, 50-3000 ppm, 75-2000 ppm, 90-1500 ppm, 100-1000 ppm, 200-750 ppm, or 250-600 ppm. According to an advantageous embodiment of the present invention, the bismuth compounds preferred as a source of bismuth (III) are water-soluble. For example, the bismuth compound may have a solubility in water of at least 0.5 wt.%, at least 1 wt.%, at least 5 wt.%, or at least 10 wt.% at 25° C. However, in other embodiments, the bismuth compound is dispersible in water, preferably to provide a storage stable dispersion, providing bismuth (III) ions in the bismuth conversion coating composition and / or bath in combination with component B).

[0043] Component B), the at least one water-soluble organic chelating agent, preferably comprises one or more water-soluble organic acids and / or salts thereof, preferably substituted and / or unsubstituted organic carboxylic acids, capable of chelating dissolved and / or dispersed bismuth. In one embodiment, component B) comprises water-soluble C3-C12, preferably C4-C9 organic acids and / or salts thereof. (Meth)acrylic monomeric acids and their salts are preferably avoided due to their tendency to polymerize in the bath. The organic acids may be aliphatic or aromatic; may be linear, branched or cyclic; may be saturated or unsaturated and may include one or more nitrogen-containing functional groups. The water-soluble organic acids may be mono-carboxylic acids, but are preferably di-, tri-, tetra- or more carboxyl groups (organic polycarboxylic acids) or those having more than one carboxyl group as long as it does not interfere with the objectives of the present invention. Having multiple carboxyl groups provides multiple donor atoms available for binding metal atoms. In a preferred embodiment, the organic polycarboxylic acids are at least bidentate, meaning that they have two donor atoms that allow them to bind to the central bismuth atom or ion at two points. Compared to two separate donors, monocarboxylic acids such as formic acid, bidentate donation is entropically favored. The water-soluble organic acid and / or salt thereof may be substituted with other functional groups such as hydroxyl groups. In one embodiment, the organic carboxylic acid may be a hydroxyl-functionalized polycarboxylic acid. In a further embodiment, the hydroxyl-functionalized polycarboxylic acid may desirably have a ratio of OH groups to COOH groups in the range of about 0.5:1 to 5:1. Desirably, component B) is present in an amount sufficient to solubilize or suspend Bi ions, for example, about 50 to 100,000 ppm, 100 to 75,000 ppm, 200 to 50,000 ppm, 250 to 25,000 ppm, 300 to 20,000 ppm, 350 to 10,000 ppm, 400 to 7,5000 ppm, 450 to 5000 ppm, or 500 to 3000 ppm.

[0044] Non-limiting examples of suitable materials for component B) include: organic acids having multiple carboxylic acid functionalities such as alpha, omega-dicarboxylic acids, such as propanedioic acid, butanedioic acid, pentanedioic acid, hexanedioic acid, heptanedioic acid, octanedioic acid, nonanedioic acid, decanedioic acid, and the like, which may further include one or more additional functionalities along the carbon chain, such as hydroxyl functionalities. Specific examples of suitable materials for component B) include tartaric acid, citric acid, ethylenediaminetetraacetic acid, and the like, as well as lactic acid, gluconic acid, gallic acid, ascorbic acid, bicine (2-(bis(2-hydroxyethyl)amino)acetic acid) and salts of any of these acids, as well as mixtures of one or more of the organic acids and salts.

[0045] Component C), copper ions, preferably copper (II) ions, may be present in the bismuth conversion coating composition in an amount of about 1-300 ppm, 1.5-200 ppm, 2-150 ppm, 3-100 ppm, 3.5-75 ppm, 4-50 ppm, 4.5-25 ppm, or 5-20 ppm. Non-existent examples of materials suitable for component C) include water-soluble and / or acid-soluble inorganic and organic copper sources such as hexafluorosilicic acid, hydroxides, nitrates, chlorides, phosphates, and sulfates, as well as acetates, citrates, formates, gluconates, tartrates, and other organic salts of copper, as well as oxides, selenites, selenites, and the like. Any inorganic or organic source of Cu(II) may be used that provides Cu(II) ions that are soluble in the conversion coating composition and can be at least partially deposited in the conversion coating on the metal substrate and that do not adversely affect the objects and advantages of the present invention. Copper(II) sulfate, copper(II) nitrate, copper(II) oxide, and copper(II) hydroxide are preferred. Combinations of two or more different copper compounds may be used.

[0046] Component D), the one or more metal etchants, may include a source of free fluoride, such as HF, and / or a complex fluoro acid, which may be present as a source of fluoride ions, preferably a complex fluoro acid or a salt thereof. Complex fluoro acids are represented by the general formula H 2 XF 6where X can be Ti, Zr, Hf, and Si, and salts of these fluoro acids may also be useful in the present invention. In general, the amount of component D) such as HF, complex fluoro acids and / or salts thereof useful in the bismuth conversion coating composition ranges from about 0-5000 ppm, 100-4500 ppm, 200-4000 ppm, 300-3500 ppm, or 400-3000 ppm, 450-2500 ppm, 500-2000 ppm, 525-1500 ppm. Component D) may desirably provide a reservoir of free fluoride ions. Generally, the amount of free fluoride useful in the bismuth conversion coating composition ranges from about 0-5000 ppm, 1-4000 ppm, 3-3000 ppm, 4-2000 ppm, 5-1000 ppm, 6-500 ppm, 8-200 ppm, or 10-100 ppm. The free and combined fluoride ions act to increase the etching of the metal substrate surface.

[0047] Component E), the pH adjuster, may be in the form of an acid, a base, or a buffer acid / base combination. The bismuth conversion coating composition preferably has a pH in the range of 2 to 6. If the pH is less than 2, etching will be excessive, resulting in insufficient film formation. If the pH is greater than 6, etching will be insufficient, resulting in poor film formation and bath components may precipitate. More preferably, the lower limit is 2.5 and the upper limit is 5.5. Even more preferably, the lower limit is 3 and the upper limit is 4. To adjust the pH of the conversion coating agent, acidic compounds such as nitric acid, sulfuric acid, basic compounds such as sodium hydroxide, potassium hydroxide, ammonia, etc. Methods for adjusting the pH level to the ranges of 2 to 6, 2.5 to 5, 2.75 to 4.5, 3 to 4 are known to those skilled in the art. The desired pH is preferably set by the addition of at least one base, more preferably at least one inorganic and / or at least one organic base. Suitable examples of pH adjusters useful in the bismuth conversion coating compositions described herein include NaOH, KOH, ammonium hydroxide, ammonium bicarbonate, ammonium carbonate, sodium bicarbonate, sodium carbonate, potassium bicarbonate, potassium carbonate, and Bi(OH).3 Examples include:

[0048] Component F), nitrate ions are desirably present and may be provided as a counterion or partial counterion to other components of the bismuth conversion coating composition, such as, but not limited to, component A), and, if present, components D) and F). Suitable sources of component F) thus include nitric acid, bismuth (III) nitrate pentahydrate; bismuth subnitrate, and copper nitrate and nitrates of Group IVB metals, with sodium nitrate and nitric acid being preferred, if a countercation is present. Nitrate ions are desirably present in an amount of about 0-10,000 ppm, 15-9000 ppm, 30-8000 ppm, 45-7000 ppm, 60-6000 ppm, 75-5000 ppm, 90-4000 ppm, 100-3500 ppm, or 75-3000 ppm. Any inorganic or organic source of nitrate ions that does not adversely affect the objectives and advantages of the present invention may be used. Combinations of two or more different nitrates may be used.

[0049] Additional components of the bismuth conversion coating composition may include:

[0050] Component G), a Group IVB metal, may be present in the bismuth conversion coating composition and the resulting coating. Desirably, the Group IVB metal may be selected from Zr, Ti, and Hf, and combinations thereof, preferably Zr and Ti. Generally, useful amounts of component G) in bismuth conversion coating compositions are about 0-500 ppm, 10-450 ppm, 20-400 ppm, 30-350 ppm, 40-300 ppm, 45-250 ppm, 50-200 ppm, 70-150 ppm. Non-existent examples of materials suitable for component G) include water-soluble and / or acid-soluble inorganic and organic sources of Group IVB metals, such as fluorotitanic acid, H 2 TiF 6 Fluorozirconate, H 2 ZrF 6 ;Zirconium basic carbonate, Zr(OH) 2 CO 3 ZrO 2 Titanium nitrate, Ti(NO3 ) 4 Titanium acetate, Ti(CH 3 COO) 2 ; Zirconium nitrate, Zr(NO 3 ) 4 ;Zirconium acetate, Zr(CH 3 COO) 2 The Group IVB metal fluoroacid may also optionally provide at least a portion of component D) as one or more metal etchants.

[0051] In the bismuth conversion coating composition, component H), one or more accelerators may be present. The conversion coating composition typically does not require the presence of an accelerator due to the relatively rapid deposition, as shown by the examples that do not contain an accelerator. Optionally, one or more coating accelerators may be included in an amount of 1 to 5000 ppm, preferably oxidizing accelerators such as peroxides, iron (III) ions, nitrite ions, hydroxylamine, persulfate ions, sulfite ions, hyposulfite ions, and halogen-based ions such as sodium chlorate. Non-existent examples of materials suitable for component H) include water-soluble and / or acid-soluble accelerators such as hydroxylamine (which may be provided as a salt such as hydroxylamine sulfate); peroxides, preferably hydrogen peroxide; sodium nitrobenzene sulfonate; sodium nitrite, nitroguanidine, oximes, and the like, which can accelerate the deposition reaction of the bismuth conversion coating composition without adversely affecting the working bath or the deposited coating. The amount of component H) will vary with the type of accelerator used, and selecting the appropriate amount is within the knowledge of one skilled in the conversion coating art. Generally, the amount of component H) useful in the bismuth conversion coating composition can range from about 0-500 ppm, 10-450 ppm, 20-400 ppm, 30-350 ppm, 40-300 ppm, 45-250 ppm, 50-200 ppm, 70-150 ppm, or for less active accelerators or accelerators whose concentration decreases rapidly, e.g., due to decomposition, the upper accelerator amount limit may include concentrations of 1000 ppm, 900 ppm, 800 ppm, 700 ppm, or 600 ppm in addition to the aforementioned ranges.

[0052] Although the bismuth conversion coating composition deposits a satisfactory bismuth coating in the absence of polymer, component I), one or more water soluble and / or water dispersible polymer components, may be advantageously included in the bismuth conversion coating composition, if desired. Generally, the amount of component I) useful in the bismuth conversion coating composition ranges from about 0-500 ppm, 10-450 ppm, 20-400 ppm, 30-350 ppm, 40-300 ppm, 45-250 ppm, 50-200 ppm, 70-150 ppm. Non-exhaustive examples of materials suitable for component I) include (i.1) polyhydroxylalkylamino derivatives of poly{p-hydroxystyrene}, which are described in more detail in U.S. Pat. No. 4,963,596, the entire disclosure of which is incorporated herein by reference except to the extent expressly stated otherwise; (i.2) epoxy polymers, in particular polymers of diglycidyl ethers of bisphenol-A, optionally end-capped with non-polymerizable groups and / or where a portion of the epoxy groups have been hydrolyzed to hydroxyl groups; (i.3) polymers and copolymers of acrylic acid, methacrylic acid and their salts; (i.4) organic polymer components selected from phenalkamine compounds, polyamidoamine compounds, catechol compounds and catechol copolymers; and (i.5) silicon-containing polymers and copolymers, which may be organic and / or inorganic polymers.

[0053] As used herein, the term "phenalkamine compound" refers to a molecule comprising a benzene ring having at least three functional groups attached to the benzene ring: a) an OH (i.e., hydroxyl) group; b) a C6-C30 saturated or unsaturated alkyl group; and c) an amine-functionalized substituent, such as an amino-alkyl substituent. According to one embodiment of the present invention, the phenalkamine compound corresponds to the following formula (I): R-Ar(-OH)-CHR'NHCH 2 CH 2 (NHCH 2 CH 2 ) n NH 2 (I) wherein Ar is a benzene ring, R is a C6-C30 straight or branched, saturated or unsaturated alkyl group, R' is H or an alkyl group (e.g., C1-C6 or C1-C3 alkyl, such as methyl, ethyl, propyl, etc.), and n is an integer that is 0, or at least 1, 2, 3, 4, 5, and no more than 20, no more than 18, no more than 16, no more than 14, no more than 12, no more than 10, no more than 8, or no more than 6, preferably 1-4.

[0054] According to one embodiment, a) and c) are ortho to each other; i.e., they are attached to adjacent carbon atoms of the benzene ring. According to a further embodiment, b) is attached to a carbon atom of the benzene ring that is at least one carbon atom away from each of the carbon atoms to which a) and c) are attached. In another embodiment, c) is ortho to the hydroxy group and b) is meta to a). The benzene ring may have one or more additional non-hydrogen substituents other than those listed in formula (I), such as alkyl groups (e.g., methyl, ethyl) and hydroxyl groups (in addition to a). For example, a second optional hydroxyl group may be present on the benzene ring in a meta position to c). In one embodiment, the phenalkamine compound may not include a hydroxyl group that is ortho to a). The amine functionalized substituent c) may include one or more amino groups, preferably primary and / or secondary amino groups, substituted on the alkylene group to which the alkylene group is attached to the benzene ring. In one embodiment, c) may contain at least one primary amino group, or optionally two or more primary and / or secondary amino groups. Mixtures or combinations of phenalkamine compounds may also be utilized. Desirably, the phenalkamine polymer has a weight average molecular weight in the range of 200-2000 Daltons. Phenalkamines are further described in co-pending International Application No. PCT / 2019 / 065127, which is incorporated herein by reference in its entirety.

[0055] As used herein, the term "polyamidoamine compound" refers to a linear or branched, saturated or unsaturated organic polymer containing multiple amide functional groups and, optionally, amine and / or imidazoline functional groups. The polymer may contain at least some imidazoline functional groups having amide linkages at the tertiary nitrogen atom, multiple branches, and / or substituents. Desirably, the polyamidopolyamine polymer has a weight average molecular weight in the range of 200 to 10,000. Polyamidoamines are described in further detail in International Patent Publication WO2016167928, which is incorporated herein by reference in its entirety.

[0056] The term "catechol compound" refers to an organic compound having an aromatic ring system that includes at least two hydroxyl groups located on adjacent carbon atoms of the aromatic ring system. As used herein, the term "catechol compound" includes catechol and catechol derivatives, such as, for example, dopamine and catecholamines, such as 3,4-dihydroxy-L-phenylalanine. "Catechol copolymer" refers to the reaction product of at least one catechol / catechol derivative with at least one co-reactant having one or more functional groups reactive therewith, where the co-reactant may be, for example, an amine, particularly a polyamine, such as polyethyleneimine, or a (meth)acrylic functionalized compound, such as methacrylamideethylethyleneurea, as well as salts and mixtures thereof. Desirably, the catechol copolymer has a weight average molecular weight in the range of 200 to 10,000 Daltons. Catechol, catechol derivatives, and polymeric reaction products are described in further detail in International Patent Publication WO2018119368, which is incorporated herein by reference in its entirety.

[0057] Other additives known in the metal pretreatment art can be included in the bismuth conversion coating compositions disclosed herein, so long as the additives do not interfere with the deposition and performance of the bismuth conversion coating. Additives include surfactants, oxidizers (different from accelerators), thickeners, rheology modifiers, dispersants, biocides, biostats, adhesion promoters, and the like.

[0058] Some materials such as metallic elements may be present in the conversion coating composition as additives or contaminants, such as metals from Groups IIB, VB-VIIB, VIII, IIIA and IVA, and Sb. These metallic elements may be used as additives, provided that the additives do not interfere with the deposition and performance of the bismuth conversion coating. In some embodiments, such metals are not intentionally added to the bismuth conversion coating compositions disclosed herein and are preferably omitted, but may be present as unavoidable contaminants.

[0059] Brighteners, such as plating brighteners, e.g., naphthalenedisulfonic acid, diphenylsulfonates, arylsulfonamides, azo dyes, and the like, are not preferred but may be included as optional components in the bismuth conversion coating compositions disclosed herein, so long as the brightener does not interfere with the deposition and performance of the bismuth conversion coating. In preferred embodiments of the bismuth conversion coating compositions disclosed herein, brighteners are not present and are generally omitted due to the cost of the product.

[0060] Manufacturing method The bismuth conversion coating composition of the present invention may be prepared using any suitable technique known in the art. In one embodiment, the bismuth conversion coating composition is prepared by combining B) at least one water-soluble organic chelating agent with water, preferably distilled water, followed by adding A) a source of dissolved and / or dispersed bismuth with stirring to form a mixture. The pH of the mixture is then adjusted to the selected bath operating pH value.

[0061] In a preferred embodiment, B) may include one or more water-soluble organic acids and the pH may be adjusted, preferably by the addition of a dilute solution of an alkaline material, such as ammonium bicarbonate, to a pH in the range of about 2 to 6. Other sources of alkalinity, such as sodium hydroxide, may be used to raise the pH, so long as they do not interfere with the deposition and performance of the conversion coating.

[0062] After adjusting the pH for operating conditions, the conversion coating composition desirably contains Bi(III) ions and may include a colloidal dispersion of bismuth particles. The bismuth conversion coating composition may include dissociated anions of water-soluble organic chelating agents based on the operating pH.

[0063] As used herein, the term "storage stable" when referring to a mixture (whether a solution or dispersion) means that after the mixture is stored in a closed container at 20°C for an observation period of at least three months, the mixture is not mechanically disturbed, does not exhibit phase separation, and does not exhibit precipitation or settling of material visible to the naked human eye.

[0064] According to an aspect of the present invention, an aqueous mixture of at least one bismuth conversion coating composition is contacted with a bare metal substrate surface. Such an aqueous mixture (which may be in the form of a solution or dispersion, and is preferably a storage stable mixture) may be formed in any suitable manner. For example, the aqueous mixture may be used directly or after diluting the aqueous mixture to a particular desired end-use concentration. While only water may be used for such dilution, it is contemplated that in other embodiments of the present invention, one or more other types of components may be included in the aqueous mixture. For example, an acid, base, or buffer may be combined with the aqueous solution to modify its pH characteristics. In certain embodiments of the present invention, the pH of the aqueous mixture when contacted with the bare metal substrate surface (i.e., when used in a working conversion coating bath) may be, for example, 2-6, 2.5-5, 2.75-4.5, 3-4.

[0065] Aqueous mixtures (working baths) that are repeatedly in contact with bare metal substrate surfaces may lose concentration of bismuth compounds and other components such as copper over time. When this occurs, the aqueous mixture in the working bath may be replenished by adding replenishers that contain individual components or combinations of components whose amounts need to be adjusted to provide an effective amount of bismuth compounds, etc. to restore the desired concentration. The compositions according to the invention may be provided in a two-pack, where part A may contain, for example, bismuth, copper, and other components that do not form precipitates with Bi and / or Cu, such as nitric acid and / or chelating agents, and part B may contain chelating agents, fluoride-containing compounds, and other components. In one embodiment, the bismuth conversion coating bath replenisher contains bismuth, copper, and nitric acid, optionally in the form of an easily dispersible slurry. Additionally, it is understood that repeatedly used working baths containing the aqueous mixture may accumulate some amount of various components carried over from the cleaning step, such as alkaline builders (sodium hydroxide, potassium hydroxide, alkali metal carbonates, alkali metal bicarbonates, phosphates, silicates), surfactants, and oil / grease / dirt contaminants. When the levels of such components reach a point that adversely affect the performance of the working bath or the quality of the conversion coated metal substrate being treated, the contents of the working bath can be discarded, replaced, or treated to remove or reduce such components or otherwise negate their effects (e.g., by pH adjustment and / or ion exchange).

[0066] Metal Substrate The present invention is particularly useful in connection with the treatment of metal substrate surfaces susceptible to corrosion, especially bare metal surfaces that are to be painted. For example, ferrous (iron-containing) metal substrates may be treated according to the present invention. Exemplary metal substrates include, but are not limited to, iron; steel substrates, such as cold-rolled steel, hot-rolled steel, stainless steel; steels coated with zinc alloys, such as zinc metal, electrogalvanized steel, galvalume, galvanneal, hot-dip galvanized steel; magnesium alloys; aluminum alloys, and aluminum-plated steel substrates. Parts or articles that include two or more metal substrates may be treated according to the procedures described herein. The present invention may also be practiced using metal substrates in which an iron-containing component or layer is covered with an iron-free metal coating (e.g., a zinc coating), and the iron-containing component or layer is exposed as a result of cutting, forming, mounting, sanding, grinding, polishing, scoring, or other similar operations.

[0067] Cleaning process As used herein, the term "bare metal substrate surface" refers to a metal surface of a metal substrate that is essentially free of any contaminants, is not conversion coated, or is not coated with any other material other than a native oxide that may be present due to the reaction of the metal element with atmospheric oxygen. According to certain aspects of the present invention, the bare metal substrate surface to be pretreated with the bismuth conversion coating composition is obtained by cleaning the metal substrate surface to remove grease, oil, dirt, or other foreign matter and contaminants using any of the cleaning procedures and materials known or conventionally used in the art, including, for example, weak or strong alkaline cleaners, neutral cleaners, and acidic cleaners. Methods for cleaning metal surfaces are described, for example, in "Metal Surface Preparation, Cleaning," by Murphy, Kirk-Othmer Encyclopedia of Chemical Technology, 2000. Aqueous and non-aqueous (i.e., organic solvent-based) cleaners may be used. Suitable cleaning agent components may include, for example, inorganic bases (e.g., alkali metal hydroxides, alkali metal carbonates, alkali metal bicarbonates), builders (e.g., phosphates, silicates), surfactants, water, organic solvents, and the like. Examples of alkaline cleaning agents include Palco® Cleaner ZX-1, Palco® Cleaner 315, and Bonderite® C-AK T51, each of which is available from Henkel Corporation, Madison Heights, Michigan. The cleaning agent may be applied to and contacted with the metal substrate surface using any suitable method, such as spraying, dipping, wiping, and the like. The cleaner temperature during contact may be, for example, about 20° C. to 60° C., but may be lower or higher without adversely affecting the process. The contact time between the cleaning agent and the metal substrate may be any time (e.g., 10 seconds to 5 minutes) effective to achieve the desired degree of contaminant removal. Mechanical action may be utilized to aid in the removal of contaminants. Typically, cleaning agents used for such purposes are in the form of liquids or solutions, although the surface of the metal substrate can also be cleaned using only mechanical means such as abrading, sandblasting, or blasting with other dry media.Following the cleaning step, the metal substrate may optionally be subjected to one or more additional steps prior to contacting with a solution or dispersion containing one or more preformed catechol compound / co-reactant reaction products. For example, the metal substrate surface may be rinsed one or more times with water and / or an acidic aqueous solution after cleaning.

[0068] The bare metal substrate surface may be prepared by any method of forming or finishing a metal article that results in a bare metal surface, such as cutting, scoring, filing, grinding, polishing, shot blasting, sanding, etc.

[0069] Chemical coating process Following the optional cleaning step, the metal substrate surface is subjected to a conversion coating step by contacting it with the bismuth conversion coating composition of the present invention, which may occur immediately after the cleaning step, or after any of the deoxidation and / or further rinsing steps mentioned above, or after an extended period of time after the cleaning step.

[0070] According to the present invention, an aqueous mixture containing a bismuth compound is contacted with the cleaned surface of a metal substrate. Such contact may be accomplished by any suitable method, such as, for example, spraying, immersion, dipping, brushing, roll coating, and the like. Typically, the aqueous mixture during such contact is maintained at a temperature ranging from ambient temperature (e.g., room temperature) to a temperature moderately above ambient temperature. For example, the temperature of the aqueous mixture in the working bath may be 10-54°C, 16-49°C, 25-36°C, or 32-43°C.

[0071] The contact time should be selected to be sufficient to deposit an effective amount of the bismuth conversion coating on the bare metal substrate surface, generally considered to be an amount effective to reduce the amount of corrosion of the metal substrate surface as measured according to ASTM B117-19, as compared to a bare metal substrate surface control measured under the same conditions. Typically, a contact time of 0.1 to 30 minutes (e.g., 8 seconds to 30 minutes, or 10 seconds to 20 minutes, or 30 seconds to 10 minutes, 1 minute to 6 minutes, 1.5 minutes to 3 minutes, or any range encompassed by the disclosed ranges) may be selected as appropriate.

[0072] Once the desired contact time with the bismuth conversion coating composition is reached, contact may be stopped and the conversion coated metal substrate may be transferred to further processing steps. For example, spraying may be stopped or the article including the conversion coated metal substrate may be removed from the immersion bath. Residual or excess aqueous mixture may be drained from the surface of the metal substrate. Removal of residual or excess aqueous solution may be accomplished by any suitable method or combination of methods, such as drip drying, squeegeeing, wiping, draining or rinsing with water. According to certain embodiments, the conversion coated metal substrate surface may be dried (e.g., air drying, heat or oven drying). In other embodiments, the conversion coated metal substrate is not dried before proceeding to further processing steps, such as sealing, painting, by non-limiting example of electrophoretic coating with paint.

[0073] Conversion coatings of the substrate metal bismuth and metal oxides deposited on metal substrates have been demonstrated to provide corrosion resistance of the final painted part equivalent to that of tricationic zinc phosphate.

[0074] In one embodiment, the bismuth conversion coating composition may be applied to the surface of a reactive metal substrate by contacting the metal substrate with the bismuth conversion coating composition for approximately 2 minutes at a temperature of 24-40° C. Contacting may be accomplished by any suitable means, including but not limited to dipping, spraying, roll coating, and the like. Contact times and temperatures may vary, but are typically less than 10 minutes, and preferably less than 5 minutes. Desirably, the contact time is at least about 1, 3, 5, 10, 15, 20, 30, 40, 50, or 60 seconds, and is no more than about 9, 8, 7, 6, 5, 4, 3, or 2 minutes. Desirably, the temperature range is at least about 21° C., 22° C., 23° C., 24° C., 25° C., 26° C., 27° C., 28° C., 29° C., 30° C., 31° C., or 32° C., and not more than about 40° C., 39° C., 38° C., 37° C., 36° C., 35° C., 34° C., or 33° C. Temperatures at least above the freezing point of the bath and up to 50° C. may be used, so long as they do not interfere with the deposition of the conversion coating or adversely affect the performance of the bismuth metal conversion coating working bath or the conversion coating.

[0075] Without being bound to a single theory, several reactions occur when a metal substrate is contacted with an aqueous acid bismuth conversion coating composition: oxidation of the substrate (M 0 →M n+ +n e , M=Fe, Zn, Al), H + The local pH increase due to the reduction of bismuth forms a mixture of the substrate elements (Fe, Zn, Al) with bismuth oxide and / or bismuth hydroxide on the metal surface of the substrate. 3+ is deposited.

[0076] Post-processing The present invention may also be part of a multi-step process in which the as-deposited bismuth conversion coating undergoes a post-treatment and / or sealing rinse prior to painting.

[0077] Non-limiting examples of suitable post-treatments include contacting the as-deposited bismuth conversion coating with an acidic aqueous post-treatment composition (e.g., a zirconium oxide deposition composition) typically comprised of one or more periodic table Group IV metals, such as Zr, Ti, and Hf, also including other components, such as metal etchants (e.g., fluorides), and optionally copper and / or nitrates and / or zinc and / or Si-based materials. The acidic aqueous post-treatment composition may, for example, have a pH of 5.0 or less and may include: 50-750 ppm of at least one Group IV metal; 0-50, 1-50, or 5-50 ppm of copper; 10-100 ppm of free fluoride; optionally, nitrates; and optionally, silanes, SiO. 2 , Si-based materials such as silicates. Optionally, the post-treatment may be a composite post-treatment further comprising a dissolved and / or dispersed organic polymer. The acidic aqueous post-treatment composition may be applied to the surface of a metal substrate having a bismuth conversion coating deposited on at least a portion of the surface for a time sufficient to contact the metal substrate with the acidic aqueous post-treatment composition to form a Group IV metal oxide on at least a portion of the metal substrate surface. Contacting may be accomplished by any suitable means, including but not limited to dipping, spraying, roll coating, and the like. Contact times and temperatures may vary, but are typically less than 10 minutes, and preferably less than 5 minutes. Desirably, the contact time is at least about 1 second, 3 seconds, 5 seconds, 10 seconds, 15 seconds, 20 seconds, 30 seconds, 40 seconds, 50 seconds, or 60 seconds, and is no more than about 9 minutes, 8 minutes, 7 minutes, 6 minutes, 5 minutes, 4 minutes, 3 minutes, or 2 minutes. Desirably, the temperature range is at least about 21° C., 22° C., 23° C., 24° C., 25° C., 26° C., 27° C., 28° C., 29° C., 30° C., or 32° C. and not more than about 40° C., 39° C., 38° C., 37° C., 36° C., 35° C., 34° C., or 33° C. Temperatures at least above the freezing point of the bath and up to 50° C. may be used as long as they do not interfere with the deposition of the conversion coating or adversely affect the performance of the bismuth metal conversion coating working bath or the conversion coating.

[0078] A suitable sealing rinse may desirably be an aqueous rinse, but may optionally include an organic solvent. The sealing rinse may contain an organic polymer, an inorganic polymer, or a combination thereof. The sealing rinse typically includes a water-soluble and / or water-dispersible polymer that can coalesce, crosslink, or form a sealing layer on the conversion coated metal substrate upon drying, with or without heating. The sealing rinse may typically have a pH of about 4-10.

[0079] Sealing rinses are distinguished from "paints" for the purposes of this invention by the following differences: The thickness of the organic sealing rinse is generally around 0.05 to 2.0 microns (wet film), while the thickness of the paint film is typically 15 to 500 microns (wet film). The organic sealing layer typically has a dry film thickness of 0.01 to 1.0 microns as measured by glow discharge optical emission spectroscopy. The paint layer has a dry film thickness of about 15 microns minimum, and generally 1 mil (25.4 microns), 1.5 mils (38.1 microns) or more, with typical vehicle paints having a total paint thickness of about 3-5 mils (76.2 to 127 microns). Organic sealing rinses typically contain up to about 0.5% by weight organic solids, while coating compositions typically contain at least about 5% and up to about 60% by weight organic solids.

[0080] Non-limiting examples of polymers suitable for use in the sealing rinse include epoxy, phenolic, acrylic, polyurethane, polyester, and polyimide, and combinations thereof. In one embodiment, an organic polymer selected from epoxy, phenolic, and polyimide is used. Preferred polymers for forming the additional layer include, for example, phenol-formaldehyde based polymers and copolymers made from novolac resins having a formaldehyde to phenol molar ratio less than 1, and resole resins having a formaldehyde to phenol molar ratio greater than 1. Such polyphenolic polymers can be made as known in the art, for example, according to U.S. Pat. No. 5,891,952. Novolac resins are desirably used in combination with a crosslinker to facilitate curing. In one embodiment, a resole resin having a formaldehyde to phenol molar ratio of about 1.5 is utilized to form the polymeric additional layer on the bismuth conversion coating. Phenolic resins useful for forming the polymeric layer desirably have a molecular weight of about 1000 to about 5000 g / mole, preferably 2000 to 4000 g / mole.

[0081] In some embodiments, the water soluble and / or water dispersible polymer may contain functional groups that react with elements in the bismuth conversion coating that can form bonds between the polymer and the coating. For example, uncured novolac and resole resins contain OH functional groups that can react with metals in the bismuth conversion coating, thereby bonding the polymer to the coating.

[0082] Optionally, silane, SiO 2Si-based materials such as bismuth conversion coatings, silicates, etc. may be used as sealants or as additives. The sealing rinse may be applied to the surface of a metal substrate having a bismuth conversion coating deposited on at least a portion of its surface by contacting the metal substrate with the sealing rinse for a time sufficient to wet the surface of the bismuth conversion coating and / or form a layer of sealant on at least a portion of the metal substrate surface. Contacting may be accomplished by any suitable means that further enhances the corrosion resistance of the conversion coated metal substrate surface.

[0083] Applying additional coatings Following the conversion coating and optionally one or more post-rinsing (or "sealing") steps, the metal substrate may be subjected to one or more further processing steps, including, among others, the application of paint or other decorative and / or protective coatings. Any such coating known in the art may be used, including, for example, electrophoretic coating (E-coating), solvent-based paints, water-based paints, powder coatings, and the like. In such applications, the bismuth conversion coating or sealer may function as a primer or anticorrosion layer.

[0084] Thus, the present invention may be practiced according to the following exemplary multi-step process: 1) Clean the metal substrate surface; 2) rinsing the cleaned (bare) metal substrate surface with an aqueous mixture consisting of the preformed catechol compound / functionalized co-reactant reaction product; 3) conversion coating the cleaned and rinsed metal substrate surface; 4) Optionally, rinsing the conversion coated metal substrate surface with water and / or a post-rinse solution or dispersion; 5) electrophoretically coating the optionally rinsed conversion coated metal substrate surface; 6) rinsing the electrophoretically coated metal substrate surface with water; and 7) Baking the rinsed electrophoretically coated metal substrate.

[0085] Although embodiments are described herein in a manner that enables a clear and concise specification to be written, it is intended and will be understood that the embodiments can be combined or separated in various ways without departing from the invention, for example, it will be understood that all preferred features described herein are applicable to all aspects of the invention described herein.

[0086] In some embodiments, the invention herein can be construed to exclude any element or process step that does not materially affect the basic and novel characteristics of the composition, article, or method. Further, in some embodiments, the invention can be construed to exclude any element or process step not specified herein.

[0087] Although the invention is illustrated and described herein with reference to specific embodiments, the invention is not intended to be limited to the details shown, but rather, various changes in the details may be made within the scope and equivalents of the claims without departing from the invention. EXAMPLES

[0088] Example 1 A conversion coating composition was prepared by combining and mixing the following: Deionized water 99.72% by weight Bismuth subnitrate;Bi 5 O(OH) 9 (NO 3 ) 4 0.08%(0.057wt% Bi) Lactic acid (88% by weight) 0.20% by weight

[0089] The pH of the mixture = 2.7. Upon adding the above mixture to the deionized water at 75% deionized water and 25% mixture, the pH increased to 3.1. The pH was increased using 10% ammonium bicarbonate solution (Bonderite® M-AD700) until a pH = 3.5 was achieved. This resulted in a clear straw colored solution containing 143 ppm Bi and 440 ppm lactic acid.

[0090] The solution was warmed to 32° C. An ACT CRS panel was immersed in the bismuth conversion coating composition (process outlined below), which resulted in a visibly black coating containing the elements Bi, O, and Fe.

[0091] Panel Coating Process: The coating samples used were bare metal panels available from ACT Laboratories, Inc. Unless otherwise stated, the coating process was as follows:

[0092] Bismuth conversion coating process Cleaning solution: Bonderite® C-AK T51 (2% v / v, 49°C, free alkalinity (hereinafter "FAlK") 5.0, 90 second spray, 10 psi) Rinse solution: Tap water (38°C, 60 seconds spray, 10 psi) Rinse solution: Deionized water (21°C, 60 seconds spray, 10 psi) Chemical coating: 32℃, immersion for 120 seconds Rinse solution: Deionized water (21°C, 60 seconds spray, 10 psi) E-coat: BASF Cathoguard 800 (35°C, 240 seconds immersion, 0.9Amps constant current ~ 230V) Rinse solution: Deionized water (24°C, 60 seconds spray, 10 psi) Paint hardening: Bake in oven (185℃, 35 minutes).

[0093] Comparative zinc phosphate coating process (Bonderite® M-ZN958) 1.5-2.0 g / m purchased from ACT Laboratories 2Pretreated zinc phosphate coated panels were used having a total metal phosphate (hopite and phosphophyllite) coating weight of 100 g / g. The zinc phosphate coating was applied according to the Henkel Technical Process Publication. Rinse solution: Deionized water (21°C, 60 seconds spray, 10 psi) E-coat: BASF Cathoguard 800 (35°C, 240 seconds immersion, 0.9Amps constant current ~ 230V) Rinse solution: Deionized water (24°C, 60 seconds spray, 10 psi) Paint hardening: Bake in oven (185℃, 35 minutes).

[0094] Glow discharge optical emission spectroscopy elemental depth profiles were obtained on panels coated in accordance with the present invention to confirm the elements present in the coating.

[0095] Example 2 A conversion coating composition was prepared by combining and mixing the following: Deionized water 92.22% by weight Bismuth subnitrate;Bi 5 O(OH) 9 (NO 3 ) 4 0.58%(0.41wt% Bi) Lactic acid (88% by weight) 7.2% by weight

[0096] The pH of the mixture = 1.97. Upon adding the above mixture to the deionized water at 95% deionized water and 5% mixture, the pH increased to 2.7. The pH was increased using 10% ammonium bicarbonate solution (Bonderite® M-AD700) until a pH = 3.5 was achieved. This resulted in a clear straw colored solution containing 209 ppm Bi and 3368 ppm lactic acid.

[0097] The solution was warmed to 32° C. This bismuth conversion coating composition was used to dip coat ACT CRS panels according to the application process described above, resulting in a visibly black coating containing the elements Bi, O, and Fe.

[0098] Example 3 A conversion coating composition was prepared by combining and mixing the following: Deionized water 59.95% by weight Fluorosilicic acid (25% by weight) 40.00% Bismuth oxide; Bi 2 O 3 0.05%(0.045wt% Bi) pH=1.10 The pH was increased using 10% ammonium bicarbonate solution (Bonderite® M-AD700) until a pH of 3.5 was achieved, resulting in a clear, colorless solution containing 450 ppm Bi and 10% fluorosilicic acid.

[0099] The solution was warmed to 32° C. This bismuth conversion coating composition was used to dip coat ACT CRS panels according to the application process described above, resulting in a visibly black coating containing the elements Bi, O, and Fe.

[0100] Example 4 0.05% Bismuth oxide Bi 2 O 3 Instead of 0.05% bismuth subnitrate Bi 5 O(OH) 9 (NO 3 ) 4 Example 3 was repeated using 10% ammonium bicarbonate solution (Bonderite® M-AD700) to obtain a mixture with pH = 1. The pH was increased using 10% ammonium bicarbonate solution until pH = 3.5 was achieved. This resulted in a clear, colorless solution containing 357 ppm Bi and 10% fluorosilicic acid.

[0101] The solution was warmed to 32° C. This bismuth conversion coating composition was used to dip coat ACT CRS panels according to the application process described above, resulting in a visibly black coating containing the elements Bi, O, and Fe.

[0102] Example 5 0.05% Bismuth oxide Bi 2 O 3 Instead of 0.05% bismuth nitrate Bi(NO 3 ) 3 Example 3 was repeated using 10% ammonium bicarbonate solution (Bonderite® M-AD700) to obtain a mixture with a pH of 1.2. The pH was increased using 10% ammonium bicarbonate solution until a pH of 3.5 was achieved. This resulted in a clear, colorless solution containing 253 ppm Bi and 10% fluorosilicic acid.

[0103] The solution was warmed to 32° C. This bismuth conversion coating composition was used to dip coat ACT CRS panels according to the application process described above, resulting in a visibly black coating containing the elements Bi, O, and Fe.

[0104] Example 6 A conversion coating composition was prepared by combining and mixing the following: Deionized water 94.25% by weight Bismuth oxide; Bi 2 O 3 0.5%(0.45wt%Bi) Tartaric acid 5.25% by weight

[0105] The pH of the mixture was 1.7. The above mixture was added to the deionized water at 95% deionized water and 5% mixture, and the pH increased to 2.7. The pH was increased using 10% ammonium bicarbonate solution (Bonderite® M-AD700) until a pH of 3.5 was achieved. This resulted in a clear, colorless solution containing 224 ppm Bi and 2625 ppm tartaric acid.

[0106] The solution was warmed to 32° C. This bismuth conversion coating composition was used to dip coat ACT CRS panels according to the application process described above, resulting in a visibly black coating containing the elements Bi, O, and Fe.

[0107] Example 7 A conversion coating composition was prepared by combining and mixing the following: Deionized water 94.17% by weight Bismuth subnitrate;Bi 5 O(OH) 9 (NO 3 ) 4 0.58%(0.41wt%Bi) Tartaric acid 5.25% by weight

[0108] The pH of the mixture was 1.7. The above mixture was added to the deionized water at 95% deionized water and 5% mixture, and the pH increased to 2.7. The pH was increased using 10% ammonium bicarbonate solution (Bonderite® M-AD700) until a pH of 3.5 was achieved. This resulted in a clear, colorless solution containing 209 ppm Bi and 2625 ppm tartaric acid.

[0109] The solution was warmed to 32° C. This bismuth conversion coating composition was used to dip coat ACT CRS panels according to the application process described above, resulting in a visibly black coating containing the elements Bi, O, and Fe.

[0110] Example 8 A conversion coating composition was prepared by combining and mixing the following: Deionized water 99.30% by weight Bismuth nitrate; Bi(NO 3 ) 3 0.10% by weight Fluorosilicic acid (25% by weight) 0.40% Tartaric acid 0.20% by weight

[0111] The mixture had a pH of 2.0. The pH was increased using 10% ammonium bicarbonate solution (Bonderite® M-AD700) until a pH of 3.5 was achieved. This resulted in a clear, colorless solution containing 506 ppm Bi, 1000 ppm fluorosilicic acid, and 2000 ppm tartaric acid.

[0112] The solution was warmed to 32° C. This bismuth conversion coating composition was used to dip coat ACT CRS panels according to the application process described above, resulting in a visibly black coating containing the elements Bi, C, O, and Fe.

[0113] Example 9 A conversion coating composition was prepared by combining and mixing the following: Deionized water 99.30% by weight Bismuth nitrate; Bi(NO 3 ) 3 0.10% by weight Fluorosilicic acid (25% by weight) 0.40% Tartaric acid 0.20% by weight Copper nitrate (1.841%Cu)0.05%

[0114] The mixture had a pH of 2.0. The pH was increased using 10% ammonium bicarbonate solution (Bonderite® M-AD700) until a pH of 3.5 was achieved. This resulted in a clear, slightly blue / green solution containing 506 ppm Bi, 10 ppm Cu, 1000 ppm fluorosilicic acid, and 2000 ppm tartaric acid.

[0115] The solution was warmed to 32° C. This bismuth conversion coating composition was used to dip coat ACT CRS panels according to the application process described above, resulting in a visibly black coating containing the elements Bi, O, C, Cu, and Fe.

[0116] Example 10 Example 9 was repeated using 0.20 wt% ascorbic acid instead of 0.20 wt% tartaric acid, resulting in a mixture with pH=2.0. The pH was increased using 10% ammonium bicarbonate solution (Bonderite® M-AD700) until pH=3.5 was achieved. This resulted in a clear, slightly blue / green solution containing 506 ppm Bi, 10 ppm Cu, 1000 ppm fluorosilicic acid, and 2000 ppm ascorbic acid.

[0117] The solution was warmed to 32° C. This bismuth conversion coating composition was used to dip coat ACT CRS panels according to the application process described above, resulting in a visibly black coating containing the elements Bi, O, Cu, and Fe.

[0118] Example 11 A conversion coating composition was prepared by combining and mixing the following: Deionized water 99.40% by weight Bismuth nitrate; Bi(NO 3 ) 3 0.10% by weight Fluorosilicic acid (25% by weight) 0.40% Citric acid 0.10% by weight Copper nitrate (1.841%Cu)0.05%

[0119] The mixture had a pH of 2.0. The pH was increased using 10% ammonium bicarbonate solution (Bonderite® M-AD700) until a pH of 3.5 was achieved. This resulted in a clear, slightly blue / green solution containing 506 ppm Bi, 10 ppm Cu, 1000 ppm fluorosilicic acid, and 1000 ppm citric acid.

[0120] The solution was warmed to 32° C. This bismuth conversion coating composition was used to dip coat ACT CRS panels following the application process described above, resulting in a visibly gray / black coating containing the elements Bi, O, C, Cu, and Fe.

[0121] Example 12 The following compositions were used to deposit bismuth conversion coatings onto bare ACT CRS substrates using the application process described above with a coating bath at 32°C. 1. Bi 2 O 3 450 ppm Bi from, 10% fluorosilicic acid; pH = 3.5; 2. 360 ppm Bi from bismuth subnitrate, 10% fluorosilicic acid; pH=3.5; 3. 250 ppm Bi from bismuth nitrate, 10% fluorosilicic acid; pH=3.5; 4. 216 ppm Bi from bismuth subnitrate, 0.3% lactic acid; pH=3.5; 5. 720 ppm Bi from bismuth nitrate, 1000 ppm fluorosilicic acid, 2000 ppm tartaric acid, 10 ppm Cu; pH=3.5.

[0122] All five of these bismuth conversion coating compositions deposited a dark black Bi conversion coating.

[0123] The alkaline resistance of these conversion coatings was evaluated by immersion in 0.1 M NaOH (pH = 12.2) for 4 hours at a temperature of 21° C. For comparison, a bare ACT CRS coated with a commercial zinc phosphate conversion coating (Bonderite® M-ZN958) was also evaluated using the same test conditions.

[0124] After exposure to NaOH, the panels were rinsed for 30 seconds and air dried using a clean compressed air source (90 psi). All ACT CRS panels coated with bismuth remained black with no evidence of red rust / iron oxidation. Bismuth loss was approximately 10% of original weight. The zinc phosphate samples were 100% covered with red rust and had significant loss of zinc phosphate coating (>50% loss of original weight). In all cases, the coating loss was identified using Glow Discharge Optical Emission Spectroscopy Elemental Depth Profiling (GDOES).

[0125] Example 13 In this example, different types of ACT metal panels (CRS, EG, HDG and Al6111 panels) were tested. A bismuth conversion coating composition according to Example 9 was made and the pH was raised using 10% ammonium bicarbonate solution (Bonderite® M-AD700) until pH=3.5 was achieved. This resulted in a clear, slightly blue / green solution containing 506 ppm Bi, 10 ppm Cu, 1000 ppm fluorosilicic acid and 2000 ppm tartaric acid. The solution was warmed to 32° C. and had 72 ppm free fluoride and a pH of 3.5.

[0126] Following the application process described above, ACT CRS, EG, HDG, and Al6111 panels were dip coated, resulting in a visibly black coating on each of the different metal substrate samples. Each bismuth conversion coating contained the elements Bi, O, C, and Cu along with metals from the respective base substrate.

[0127] Example 14 A conversion coating composition was prepared by combining and mixing the following: Deionized water 99.30% by weight Fluorosilicic acid (25% by weight) 0.40% Tartaric acid 0.20% by weight Bismuth subnitrate;Bi 5 O(OH) 9 (NO 3 ) 4 0.07% Glycoluril resin 200ppm Copper nitrate (1.841%Cu)0.05%

[0128] The mixture had a pH of 1.97. The pH was increased using 10% ammonium bicarbonate solution (Bonderite® M-AD700) until a pH of 3.5 was achieved. This resulted in a clear, slightly blue / green solution containing 506 ppm Bi, 10 ppm Cu, 200 ppm glycoluril resin, 1000 ppm fluorosilicic acid, and 2000 ppm tartaric acid.

[0129] The solution was warmed to 32° C. This bismuth conversion coating composition was used to dip coat ACT CRS panels according to the application process described above, resulting in a visibly black coating containing the elements Bi, O, C, Cu, and Fe on the CRS substrate.

[0130] Example 15 A conversion coating composition was prepared by combining and mixing the following: Deionized water 99.30% by weight Fluorosilicic acid (25% by weight) 0.40% Tartaric acid 0.20% by weight Bismuth subnitrate;Bi 5 O(OH) 9 (NO 3 ) 4 0.07% Copper nitrate (1.841%Cu)0.05% Sodium nitrobenzene sulfonate, (SNBS) 100ppm

[0131] The mixture pH=2.08. The pH was increased using 10% ammonium bicarbonate solution (Bonderite® M-AD700) until pH=3.5 was achieved. This resulted in a clear, slightly blue / green solution containing 506 ppm Bi, 100 ppm SNBS, 1000 ppm fluorosilicic acid, and 2000 ppm tartaric acid.

[0132] The solution was warmed to 32° C. This bismuth conversion coating composition was used to dip coat ACT CRS panels according to the application process described above, resulting in a visibly black coating containing the elements Bi, O, C, Cu, and Fe.

[0133] (Example 16) In this example, different types of ACT metal panels (CRS, EG, HDG and Al6111 panels) were coated and tested. The conversion coating compositions were prepared by combining and mixing the following: Deionized water 99.28% by weight Bismuth subnitrate;Bi 5 O(OH) 9 (NO 3 ) 4 0.07% Fluorosilicic acid (25% by weight) 0.40% Tartaric acid 0.20% by weight Copper nitrate (1.841%Cu) 0.05%

[0134] The pH of the mixture was 2.08. The pH was increased using 10% ammonium bicarbonate solution (Bonderite® M-AD700) until a pH of 3.5 was achieved. This resulted in a clear, slightly blue / green solution containing 506 ppm Bi, 10 ppm Cu, 1000 ppm fluorosilicic acid, and 2000 ppm tartaric acid. The mixture also contained undissolved bismuth subnitrate (a white solid).

[0135] ACT CRS, EG, HDG, and Al6111 panels were dip coated according to the application process described above. This resulted in a visibly black coating on each of the different metal substrate samples. Each bismuth conversion coating contained the elements Bi, O, C, and Cu along with the metals from the respective base substrate. After application of the bismuth conversion coating, the panels were painted with cathodic electrocoat, BASF CasoGuard 800, without drying or stopping the process, according to the parameters set forth above for the bismuth conversion coating, E-coat process. Paint time = 4.0 minutes. For comparison, ACT panels coated with a commercial tricationic zinc phosphate (Bonderite® M-ZN958) were coated with the zinc phosphating process described above, including E-coating with BASF CasoGuard 800 using the same application parameters.

[0136] The E-coat appearance of the bismuth conversion coated panels was smooth, uniform, and free of mapping defects. The cured paint color of the bismuth conversion coated panels was visibly darker than the zinc phosphate coated control panels. Dry E-coat thickness was measured with the bismuth conversion coating providing a comparable thickness to the zinc phosphate control panels.

[0137] [Table 1]

[0138] paint adhesion Paint adhesion was evaluated using GMW14829 / 14704. Procedure GMW14704 involves three separate tests: initial crosshatch, crosshatch following 24 hours of water immersion, and crosshatch following 48 hours of water immersion. Each crosshatch is followed by a tape pull as defined by General Motors test methods, with higher percentage numbers indicating better performance. Panels were tested in triplicate. Different panels were used for the 24 hour and 48 hour immersion tests.

[0139] [Table 2]

[0140] Paint adhesion to the bismuth coating is comparable to the zinc phosphate control.

[0141] Corrosion Performance Cyclic corrosion performance was evaluated using GMW14872, Exposure C (26 cycles, mass loss = 3.892 g). The test cycle was defined by General Motors test method and included a series of exposures to humidity, water fog, and salt spray. The painted panels were scribed and subjected to 26 cycles. Panels were tested in triplicate.

[0142] [Table 3]

[0143] Corrosion resistance for the bismuth coating is comparable to the zinc phosphate control.

[0144] The coating weight and thickness of the bismuth conversion coating on several unpainted panels were characterized. The average bismuth conversion coating weight, measured as bismuth, was determined using Niton Xl3t (X-ray fluorescence) and the coating thickness was determined using glow discharge optical emission spectroscopy elemental depth (depth profiling).

[0145] [Table 4]

[0146] (Example 16') Modified Washing Example 16 above was repeated on a second set of ACT panels with the following process modification: the single "clean" step of spraying Bonderite® C-AK T51 for 90 seconds was replaced with two consecutive "clean" steps: 1) spraying Bonderite® C-AK T51 at 10 psi for 60 seconds immediately followed by 2) immersion in Bonderite® C-AK T51 for 120 seconds. After the bismuth conversion coating and rinsing, the properties of the bismuth conversion coating on some of the unpainted panels were evaluated. The average bismuth-equivalent coating weight, measured as bismuth, was determined using Nitron X13t (X-ray fluorescence) and the coating thickness was determined using glow discharge optical emission spectroscopy elemental depth (depth profiling).

[0147] [Table 5]

[0148] The E-coat appearance of the bismuth conversion coated panels was smooth and uniform with no mapping defects. The cured paint color of the bismuth conversion coated panels was visibly darker than the zinc phosphate painted control panels. Dry E-coat thickness was measured with the bismuth conversion coating providing a comparable thickness to the zinc phosphate control panels.

[0149] [Table 6]

[0150] Corrosion Performance The Example 16' panels were evaluated for cyclic corrosion performance using GMW14872, with Exposure C modified and used: (29 cycles, mass loss = 4.065 g).

[0151] [Table 7]

[0152] Using a different test, the cyclic corrosion performance of the panels of Example 16' was evaluated using Ford L-467. The test cycle was defined by the Ford Motor Company test method and included a series of exposures to humidity, water mist, and salt spray. The painted panels were scribed and tested for a period of six weeks. The panels were tested three times.

[0153] [Table 8]

[0154] (Example 17) Example 16 was repeated with a reduced amount of tartaric acid (reduced from 0.20 wt.% to 0.108 wt.%). The mixture had a pH of 2.0. The pH was increased using 10% ammonium bicarbonate solution (Bonderite® M-AD700) until a pH of 3.5 was achieved. This resulted in a clear, slightly blue / green solution containing 506 ppm Bi, 10 ppm Cu, 1000 ppm fluorosilicic acid, and 1080 ppm tartaric acid. The solution was clear with no undissolved (visible) solids.

[0155] Following the procedure of Example 16 resulted in ACT CRS, EG, HDG, and Al6111 panels with visibly black coatings on each of the different metal substrate samples. Each bismuth conversion coating contained elements Bi, O, C, and Cu, as well as metals from the respective base substrate. The E-coat appearance was smooth and uniform with no mapping defects. The cured paint color of the bismuth conversion coated panels was visibly darker than the zinc phosphate coated control panels. The E-coat dry film thickness was comparable between the bismuth coatings and the zinc phosphate coated control. Zero soak and 48 hour soak paint adhesion and corrosion resistance tests were performed according to the procedure of Example 16, with the results shown in the table below.

[0156] [Table 9]

[0157] Paint adhesion to the bismuth coatings is comparable to the zinc phosphate control, except for the EG and HDG substrates.

[0158] [Table 10]

[0159] The corrosion resistance of the bismuth coating is comparable to the zinc phosphate control.

[0160] (Example 18) Example 16 was repeated with an increased amount of tartaric acid (from 0.20% to 0.54% by weight). The mixture had a pH of 2.0. The pH was increased using 10% ammonium bicarbonate solution (Bonderite® M-AD700) until a pH of 3.5 was achieved. This resulted in a clear, slightly blue / green solution containing 506 ppm Bi, 10 ppm Cu, 1000 ppm fluorosilicic acid, and 5400 ppm tartaric acid. The solution was clear with no undissolved (visible) solids.

[0161] Following the procedure of Example 16 resulted in ACT CRS, EG, HDG, and Al6111 panels with visibly black coatings on each of the different metal substrate samples. Each bismuth conversion coating contained the elements Bi, O, C, and Cu, as well as metals from the respective base substrate. The bismuth conversion coatings on the CRS substrates were examined using field emission scanning electron microscopy (FESEM) at a maximum magnification of 100,000x. The bismuth conversion coatings deposited on the CRS showed an intact substrate coating layer with uniform nodular structure. No exposed CRS substrate was observed. The E-coat appearance was smooth and uniform with no mapping defects. The cured paint color of the bismuth conversion coated panels was visibly darker than the zinc phosphate coated control panels. The E-coat dry film thickness was comparable between the bismuth coatings and the zinc phosphate coated control. Zero soak and 48 hour soak paint adhesion and corrosion resistance tests were performed according to the procedure of Example 16, with the results shown in the following table.

[0162] [Table 11]

[0163] Paint adhesion on the bismuth coatings is comparable to the zinc phosphate control, except for the EG substrate.

[0164] [Table 12]

[0165] The corrosion resistance of the bismuth coating is comparable to the zinc phosphate control.

[0166] (Example 19) Example 16 was repeated using 0.10 wt% sodium gluconate instead of 0.20 wt% tartaric acid, resulting in a mixture with pH=2.0. The pH was increased using 10% ammonium bicarbonate solution (Bonderite® M-AD700) until pH=3.5 was achieved. This resulted in a clear, slightly blue / green solution containing 506 ppm Bi, 10 ppm Cu, 1000 ppm fluorosilicic acid, and 1000 ppm sodium gluconate. The solution was clear with no undissolved (visible) solids.

[0167] Following the procedure of Example 16 resulted in ACT CRS, EG, HDG, and Al6111 panels with visibly black coatings on each of the different metal substrate samples. Each bismuth conversion coating contained the elements Bi, O, C, and Cu along with the metals from the respective base substrate.

[0168] (Example 20) A conversion coating composition was prepared by combining and mixing the following: Deionized water 99.30% by weight Fluorosilicic acid (25% by weight) 0.40% Tartaric acid 0.20% by weight Bismuth subnitrate;Bi 5 O(OH) 9 (NO 3 ) 4 0.07% Polyamidoamine resin 0.005%

[0169] A polyamidoamine polymeric additive is Versamid 150, commercially available from Gabriel Performance Products, and is described as being the reaction product of dimerized fatty acids and polyamines; MW: 200-10,000 Daltons; amine content: 100-1000 mg KOH per gram of resin.

[0170] The mixture had a pH of 2.0. The pH was increased using 10% ammonium bicarbonate solution (Bonderite® M-AD700) until a pH of 3.5 was achieved. This resulted in a slightly yellow solution containing 506 ppm Bi, 50 ppm polyamidoamine resin, 1000 ppm fluorosilicic acid, and 2000 ppm tartaric acid. The solution was clear with no undissolved (visible) solids.

[0171] The solution was warmed to 32°C. Following the application process described above, ACT CRS, EG, HDG, and Al6111 panels were dip coated. This resulted in a visibly black coating on each of the different metal substrate samples. Each bismuth conversion coating contained the elements Bi, O, and C along with metals from the respective base substrate.

[0172] Example 21 Example 20 was repeated using 0.005% phenalkamine resin, a resin based on cashew nut shell liquid (cardanol, cardol, anacardic acid) and polyamines, commercially available from Kaldrite, Inc. under the trade name Kaldrite NX-8101, instead of 0.005% polyamidoamine resin, MW: = 200-2,000 Daltons; amine content: 100-500 mg KOH per gram of resin, to obtain a pH = 2.0 mixture. The pH was increased using 10% ammonium bicarbonate solution (Bonderite® M-AD700) until a pH = 3.5 was achieved. This resulted in a solution of a slightly yellow solution containing 506 ppm Bi, 50 ppm phenalkamine resin, 1000 ppm fluorosilicic acid, and 2000 ppm tartaric acid. The solution was clear with no undissolved (visible) solids.

[0173] The solution was warmed to 32°C. Following the application process described above, ACT CRS, EG, HDG, and Al6111 panels were dip coated. This resulted in a visibly black coating on each of the different metal substrate samples. Each bismuth conversion coating contained the elements Bi, O, and C along with the metals from the respective base substrate.

[0174] Example 22 Example 16 was repeated with the addition of Ludox TMA, an aqueous dispersion of colloidal silica (20%) available from Grace Material Technologies, in an amount of 0.025% to obtain a mixture with a pH of 2.0. The pH was increased using a 10% ammonium bicarbonate solution (Bonderite® M-AD700) until a pH of 3.5 was achieved. This resulted in a mixture with 506 ppm Bi, 10 ppm Cu, 50 ppm SiO 2 A clear, slightly blue / green solution was obtained containing 1000 ppm fluorosilicic acid and 2000 ppm tartaric acid. The solution was clear and had no undissolved (visible) solids.

[0175] The solution was warmed to 32°C. Following the application process described above, ACT CRS, EG, HDG, and Al6111 panels were dip coated. This resulted in a visibly black coating on each of the different metal substrate samples. Each of the bismuth conversion coatings contained the elements Bi, O, C, Si, and Cu as well as metals from their respective base substrates.

[0176] Post-treatment after bismuth conversion coating (Example 23) Zirconium-containing post-treatment In this example, a zirconium-containing post-treatment was applied to ACT CRS, EG, HDG, and Al6111 panels with a bismuth conversion coating to evaluate compatibility with the bismuth conversion coating layer.

[0177] This bismuth conversion coating composition of Example 16 was used to dip coat ACT CRS, EG, HDG, and Al6111 panels according to the application process described above, followed by spray deposition of a zirconium-containing post-treatment according to the following process.

[0178] Bismuth conversion coating / Post-treatment process Cleaning solution: Bonderite® C-AK T51 (2% v / v, 49°C, FAlK5.0, 90 sec spray, 10 psi) Rinse solution: Tap water (38°C, 60 seconds spray, 10 psi) Rinse solution: Deionized water (21°C, 60 seconds spray, 10 psi) Chemical coating: 32℃, immersion for 120 seconds Rinse solution: Deionized water (21°C, 60 seconds spray, 10 psi) Post-treatment: Bonderite® M-PT54NC, acidic, chromium-free, zirconium-containing passivation post-treatment (0.5% v / v, 21° C., pH=4.0, 60 sec spray) Rinse solution: Deionized water (24°C, 60 seconds spray, 10 psi) Air dry (ambient temperature, compressed air, 90 psi)

[0179] A visibly black coating was deposited on each of the ACT CRS, EG, HDG, and Al6111 metal substrate samples. Each bismuth conversion coating contained the elements Bi, O, C, and Cu along with metals from the respective base substrate. The bismuth conversion coating was not significantly removed by reaction with the zirconium-containing post-treatment composition, indicating that an acidic post-treatment can be performed after the bismuth conversion coating.

[0180] (Example 24) Organic polymer sealant The coating process of Example 23 was repeated using an organic polymer sealant in place of the zirconium-containing post-treatment. To evaluate compatibility with the bismuth conversion coating layer, the organic polymer sealant was applied to ACT CRS, EG, HDG, and Al6111 panels with bismuth conversion coating.

[0181] ACT CRS, EG, HDG, and Al6111 panels were dip coated using the bismuth conversion coating composition according to the application process of Example 23, followed by spray deposition of 0.75% v / v Bonderite® M-PT99X, an organic polymer sealant, using the following parameters: 21° C., pH=4.0, 60 second spray.

[0182] A visibly black coating was deposited on each of the ACT CRS, EG, HDG, and Al6111 metal substrate samples. Each bismuth conversion coating contained the elements Bi, O, C, and Cu along with metals from the respective base substrate. The bismuth conversion coating was not significantly removed by contact / reaction with the organic polymer sealant composition, indicating that the bismuth conversion coating may be suitable for organic polymer sealing if desired.

[0183] (Example 24') Organic Polymer Sealant Example 24 above was repeated on a second set of the ACT panels above with the following process modifications: the single "wash" step of spraying with Bonderite® C-AK T51 for 90 seconds was replaced with two successive "wash" steps: 1) spray with Bonderite® C-AK T51 at 10 psi for 60 seconds, immediately followed by 2) a 120 second dip in Bonderite® C-AK T51 and the "air dry" was replaced with "E-coat: BASF Casoguard 800 (35° C., 270 second dip, 0.9 Amps constant current to 230V), Rinse: deionized water (24° C., 60 second spray, 10 psi) and Paint cure: oven bake (185° C., 35 minutes).

[0184] ACT CRS, EG, HDG, and Al6111 panels were dip coated as described above. This resulted in a visibly black coating on each of the different metal substrate samples. Each bismuth conversion coating contained the elements Bi, O, C, and Cu along with the metals from each base substrate. To evaluate corrosion performance, the panels were painted with a cathodic electrocoat, BASF Kasogard 800, following the parameters described above for the bismuth conversion coating, E-coat process, without drying or stopping the process. Paint time = 4.5 minutes.

[0185] The E-coat appearance of the bismuth conversion coated panels was smooth and uniform with no mapping defects. The cured paint color of the bismuth conversion coated panels was visibly darker than the zinc phosphate coated control panels. Dry E-coat thickness was measured with the bismuth conversion coating providing a comparable thickness to the zinc phosphate control panels.

[0186] [Table 13]

[0187] Corrosion Performance The Example 24' panels were evaluated for cyclic corrosion performance using GMW14872, with Exposure C modified and used: (29 cycles, mass loss = 4.065 g).

[0188] [Table 14]

[0189] Using another test, the cyclic corrosion performance of the panels of Example 24' was evaluated using Ford L-467. The test cycle is defined by the Ford Motor Company test method and includes a series of exposures to humidity, water mist, and salt spray. The painted panels were scribed and tested for a period of six weeks. The panels were tested three times.

[0190] [Table 15]

[0191] The foregoing invention has been described in accordance with the relevant legal standards, and therefore the description is exemplary rather than limiting in nature. Variations and modifications to the disclosed embodiments may become apparent to those skilled in the art and are within the scope of the invention. Accordingly, the scope of legal protection given to the invention can only be determined by studying the following claims.

Claims

1. A) dissolved and / or dispersed bismuth; B) at least one water-soluble organic chelating agent present in an amount sufficient to solubilize or disperse A); C) dissolved copper ions; Including, An acidic aqueous bismuth conversion coating composition having a pH in the range of about 2.0 to about 6.

2. 10. The acidic aqueous bismuth conversion coating composition of claim 1, wherein A) comprises at least one dissolved Bi(III) and dissolved and / or dispersed bismuth compound, and B) comprises one or more water soluble organic acids and salts thereof.

3. 2. The acidic aqueous bismuth conversion coating composition of claim 1, wherein the one or more water soluble organic acids and salts thereof are selected from aliphatic or aromatic; linear, branched or cyclic; saturated or unsaturated C3 to C12 organic acids and salts thereof.

4. 3. The acidic water-based bismuth conversion coating composition of claim 2, wherein the one or more water-soluble organic acids and salts thereof comprise at least one organic polycarboxylic acid and salts thereof.

5. 5. The acidic aqueous bismuth conversion coating composition of claim 4, wherein said at least one organic polycarboxylic acid and salt thereof comprises a substituted and / or unsubstituted alpha, omega-dicarboxylic acid.

6. 6. The acidic water-based bismuth conversion coating composition of claim 5, wherein the substituted and / or unsubstituted alpha, omega-dicarboxylic acids and salts thereof comprise one or more substituted and / or unsubstituted propanedioic acid, butanedioic acid, pentanedioic acid, hexanedioic acid, heptanedioic acid, octanedioic acid, nonanedioic acid, decanedioic acid and salts thereof.

7. 3. The acidic water-based bismuth conversion coating composition of claim 2, wherein the one or more water-soluble organic carboxylic acids and salts thereof comprise tartaric acid and salts thereof.

8. 10. The acidic aqueous bismuth conversion coating composition of claim 1 comprising less than 1 wt. % phosphorus-containing acids and / or salts thereof and less than 1 wt. % nickel.

9. 10. The acidic aqueous bismuth conversion coating composition of claim 1, comprising one or more additional components selected from the group consisting of free fluoride, nitrates, and sources of Si-based materials.

10. 10. The acidic aqueous bismuth conversion coating composition of claim 1, wherein the acidic aqueous bismuth conversion coating composition comprises at least one pH adjuster and has a pH of about 2.5 to about 5.

0.

11. 10. The acidic aqueous bismuth conversion coating composition of claim 1, wherein the dissolved and / or dispersed bismuth is present in a total concentration of about 5 to 10,000 ppm.

12. 10. The acidic aqueous bismuth conversion coating composition of claim 1, wherein the dissolved and / or dispersed bismuth comprises one or more of bismuth nitrate, oxide and hydroxide.

13. 2. The acidic aqueous bismuth conversion coating composition of claim 1, wherein the dissolved and / or dispersed bismuth is selected from bismuth nitrate, bismuth nitrate pentahydrate, bismuth nitrite, bismuth oxide, bismuth hydroxide, and combinations thereof.

14. 10. The acidic water-based bismuth conversion coating composition of claim 1, wherein said at least one water soluble organic chelating agent is present in a total concentration of about 50 to 100,000 ppm.

15. 13. A replenisher composition for replenishing the acidic aqueous bismuth conversion coating composition of claim 1 after use, comprising a storage stable composition comprising bismuth, copper, nitric acid, and optionally nitrate ions.

16. a) contacting a metal surface of a substrate, preferably selected from ferrous metals, zinc-containing metals and aluminum-containing metals, with the acidic aqueous bismuth conversion coating composition of claim 1 for a time sufficient to form a bismuth conversion coating layer on at least a portion of said metal surface; b) rinsing the bismuth conversion coating layer with a rinse solution comprising water; 1. A method for depositing a bismuth conversion coating on a substrate having a metallic surface, comprising:

17. 17. The method for depositing a bismuth conversion coating according to claim 16, further comprising the step c) of subjecting at least a portion of the metal surface having the bismuth conversion coating layer to a post-treatment and / or sealing rinse before painting.

18. 18. The method of claim 16 or 17, comprising painting at least a portion of a metal surface having a bismuth conversion coating layer with a cathodically depositable electrophoretic dip coating, wherein after rinsing step b) the metal surface is not dried before being coated with the cathodically depositable electrophoretic dip coating.

19. 1. A substrate having a metal surface including a bismuth conversion coating layer deposited thereon, said bismuth conversion coating layer comprising bismuth oxide and / or bismuth hydroxide, and further comprising at least one of the elements Cu, Cu(I) and Cu(II).

20. A) dissolved and / or dispersed bismuth; B) a complex fluoroacid, preferably fluorosilicic acid, present in an amount sufficient to solubilize or disperse A); C) dissolved copper ions, and at least one pH adjusting agent in the form of an acid, base, or buffer acid / base combination, present in an amount sufficient to provide the composition with a pH in the range of about 2.0 to 6.0; 1. An acidic water-based bismuth conversion coating composition comprising:

Citation Information

Patent Citations

  • Method for forming multilayer coating film and coated article

    CN101691666A

  • Surface-treated black ferrous metal material and manufacturing method thereof

    JP2011058032A

  • Chemical conversion coating agent, membrane manufacturing method, metallic material having membrane, and coated metallic material

    JP2017048448A

  • Surface treatment agent, surface treatment method, and surface treated metal material

    JP2017048449A

  • Metal material with a bismuth film attached and method for producing same, surface treatment liquid used in said method, and cationic electrodeposition coated metal material and method for producing same

    WO2009145088A1